2011
DOI: 10.2131/jts.36.221
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin potentially attenuates the gene expression of pituitary gonadotropin .BETA.-subunits in a fetal age-specific fashion: a comparative study using cultured pituitaries

Abstract: -Our previous studies have demonstrated that maternal exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) causes a reduction in gonadotropin biosynthesis in the fetal pituitary, resulting in the attenuated expression of steroidogenic proteins in the fetal gonads and the impairment of sexual behaviors in adulthood. However, the mechanism of the attenuation remains unknown. To address this issue, we investigated whether TCDD affects the pituitary production of gonadotropins, using cultured pituitary. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, this point is controversial in light of the results of Trewin et al, which do not show any alterations with short-term hormone release from adult female rat hypothalamic and pituitary explants, following exposure to 3.1 nM TCDD in the perfusion medium [ 64 ]. In terms of signaling, it has been hypothesized that GnRH can stimulate the activity of two protein kinases A and C (PKA and PKC), to increase gonadotropin expression, and that those two pathways are then be targeted by TCDD [ 65 ]. Moreover, the inhibition of GnRH release by TCDD can be relieved by co-treatment with lipoic acid, a cofactor of several mitochondrial enzymes.…”
Section: Disruption Of Neuroendocrine Functions By Ahr Ligandsmentioning
confidence: 99%
“…However, this point is controversial in light of the results of Trewin et al, which do not show any alterations with short-term hormone release from adult female rat hypothalamic and pituitary explants, following exposure to 3.1 nM TCDD in the perfusion medium [ 64 ]. In terms of signaling, it has been hypothesized that GnRH can stimulate the activity of two protein kinases A and C (PKA and PKC), to increase gonadotropin expression, and that those two pathways are then be targeted by TCDD [ 65 ]. Moreover, the inhibition of GnRH release by TCDD can be relieved by co-treatment with lipoic acid, a cofactor of several mitochondrial enzymes.…”
Section: Disruption Of Neuroendocrine Functions By Ahr Ligandsmentioning
confidence: 99%
“…Our previous studies demonstrated that maternal treatment with TCDD at the late gestational stage attenuates the pituitary production of luteinizing hormone (LH), a primary regulator of gonadal steroidogenesis, during the perinatal stage (Mutoh et al, 2006;Taketoh et al, 2007;Takeda et al, 2009Takeda et al, , 2011Takeda et al, , 2012Koga et al, 2012). More specifically, treating pregnant Wistar rats at gestational day (GD) 15 with 1 mg/kg TCDD transiently reduces the expression of LH in both pituitary mRNA and circulating hormone levels during a period from GD20 to postnatal day (PND) 0 .…”
Section: Introductionmentioning
confidence: 99%